CKD-MBD: from the Pathogenesis to the Identification and Development of Potential Novel Therapeutic Targets - Elias, Rosilene Motta (2018)
Purpose of Review: Although we have seen tremendous advances in the comprehension of CKD-MBD pathophysiology during the last few years, this was not accompanied by a significant change in mortality rate and quality of life. This review will address the traditional and updated pathophysiology of CKD-MBD along with the therapeutic limitations that affect CKD-MBD and proposed alternative treatment targets. Recent Findings: An innovative concept brings the osteocyte to the center of CKD-MBD pathophysiology, in contrast to the traditional view of the skeleton as a target organ for disturbances in calcium, phosphate, parathyroid hormone, and vitamin D. Osteocytes, through the synthesis of FGF-23, sclerostin, among others, are able to interact with other organs, making bone an endocrine organ. Thus, osteocyte dysregulation might be an early event during the course of CKD. Summary: This review will revisit general concepts on the pathophysiology of CKD-MBD and discuss new perspectives for its treatment.